Analysis Violation of The Cooperation Principle in Coraline Children's Storybook - Khadeja Gina Alifia; Eva Utami Durahman; Cecep Agus (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This study aims to identify and categorize types of violations of Grice's maxims in the children's book Coraline, written by Neil Gaiman in 2008. A qualitative descriptive method was used to analyze the data, using the basic theories of Paul Grice (1989), White (1990), and George Yule (1996). The data consisted of 17 dialogues from the novel Coraline. Paul Grice identified that the cooperative principle has four maxims, namely quantity, quality, relation, and manner. This study focused on violations in the non-observance category. The researcher found that violations of the maxim of quantity were more dominant, followed by the maxims of manner, relation, and quality. This emphasizes that the novel Coraline has long-winded dialogues that contrast sharply with the lack of important information at times of increasing tension.